Primary Exploration of Efficacy of Community-Family Management Mode under Internet-Based Mobile Terminal Monitoring in Elderly Patients with Stable Coronary Heart Disease. (25th January 2022) - Li, Xiang; Zheng, Wenwu; Li, Jinsong; Gao, Yibin; Lin, Qiang; Yang, Jinfeng; Huang, Shuiying; Wang, Defang; Wang, Bin
Abstract : Objective . To explore the efficacy of community-family management mode under Internet-based mobile terminal (MT) monitoring in stable coronary heart disease (CHD) in the elderly. Methods . A total of 86 patients with stable CHD treated in our hospital from May 2018 to May 2021 were selected as the study objects for the retrospective study and were divided into the control group (routine intervention) and the research group (community-family management mode intervention under Internet MT monitoring) according to the health management modes, with 43 cases each, and the health behaviors and control of CHD were compared between the two groups. Results . No statistical between-group differences in general information were observed (P > 0.05 ); 6 months after intervention, the control of laboratory indexes including blood pressure, blood glucose, triglyceride, and total cholesterol in patients was obviously better in the research group than in the control group (P > 0.05 ); after intervention, the scores on rehabilitation knowledge level and secondary prevention behavior were obviously higher in the research group than in the control group (P > 0.05 ); 6 months after intervention, the scores on physical limitation, anginal stabilization, anginal frequency, disease perception, and treatment satisfaction were obviously higher in the research group than in the control group (P > 0.05 ); compared with the control group within 1 year of intervention, the readmission rate of the research group was significantly lower (P > 0.05 ); and compared with the control group, the total score of CQQC and scores on physical strength, condition, general life, and social mentality were significantly better in the research group (P > 0.05 ). Conclusion . Community-family management mode under Internet-based MT monitoring is the valid continuation of clinical nursing for elderly patients with stable CHD, which plays an effective role in terms of daily monitoring indexes, stabilizing condition, improving disease cognition, reducing the readmission rate, and improving the prognostic quality of life of patients.